Effect of photoperiod-sensitivity on yield and yield components of three sorghum varieties grown in West Africa - (:unkn) unknown (My University, 2004)
Summary Effect of photoperiod-sensitivity on yield and yield components of three sorghum varieties grown in West Africa West African sorghums are highly photoperiod-sensitive because this character has given them a great evolutionary advantage under the continental climate of the area, with large inter-annual variation in the amount and distribution of rainfall. This adaptation must be maintained in improved varieties for the region. But with the exception of variation in the duration of the vegetative cycle, few studies have examined physiological aspects of photoperiod-sensitivity in tropical cereals and this trait has been generally discarded until now. An ecophysiological study has been carried out on three sorghum varieties representative of material cropped in West Africa to quantify their physiological photoperiod-sensitivity. Experiments were done at Samanko, Mali, under natural environment over 2.5 years. Original conclusions on the development and growth of photoperiod-sensitive sorghum have been found, mainly due to the highly contrasting behaviour of the guinea race variety, which originated from West Africa: - The triggering of panicle initiation depends on both the photoperiod and the rate of change in daylength or of its components the time of sunrise or sunset. - The rates of apical leaf production varies with photoperiod and its variation at emergence, either the rate of change of daylength or the change in the time of sunrise or sunset. Initial developmental rates acquired at emergence remain constant until a sudden slowdown occurring around the date of the initiation of the 23rd leaf. This coincides with the onset of stem elongation, which occurs before panicle initiation. - Internode elongation is triggered by the sufficient availability of biosynthates related with a fast inherent LAI increase. All the developmental and growth rates slow down simultaneously probably as a consequence of the stem trophic competition and in respect wi
Keywords: African Research